Discriminant analysis of post-thaw sperm cryotolerance among three chicken breeds in a hot, humid tropical environment - Ojo Temidayo Stephen; Oke Oyegunle Emmanuel; Logunleko Mariam Opeyemi; Adekunle Ezekiel Oluwafemi; Daramola James Olamitibo; Wheto Mathew; Durosaro Samuel Olutunde; Oyewusi Joshua Adeoye; Ndubuisi-Ogbonma Lois Chidina (Universitas Airlangga, 2026)
Sperm cryopreservation is a practical reproductive technique, with variations in post-thaw sperm quality observed among different breeds. Discriminant functions can be used to distinguish breed-specific responses to cryotolerance. This study applied multivariate discriminant analysis to evaluate post-thaw sperm cryotolerance among three chicken breeds under hot, humid tropical conditions. Semen samples collected from Funaab Alpha, Arbor Acre, and Dominant Black chickens were cryopreserved and assessed for sperm viability parameters.The STEPDISC, CANDISC, and DISCRIM procedures were used to evaluate breed differentiation, canonical variables, and Mahalanobis distances among the breeds, respectively. Significant breed differences (p <0.01) were observed in seminal leukocyte count, acrosome integrity, sperm viability, and midpiece and tail abnormalities. Stepwise discriminant analysis identified sperm motility, sperm viability, malondialdehyde (MDA) concentration, leukocyte count, acrosome integrity, and midpiece and tail abnormalities as the most important variables distinguishing the three breeds. Canonical discriminant analysis revealed two canonical variables, with CAN1 accounting for 66.94% and CAN2 accounting for 33.06% of the total variation.Arbor Acre and Funaab Alpha chickens exhibited the greatest Mahalanobis distance. These findings indicate that the discriminant functions identified in this study can effectively differentiate post-thaw sperm cryotolerance among the three chicken breeds.